2021
DOI: 10.1136/jitc-2021-002875
|View full text |Cite|
|
Sign up to set email alerts
|

Aged neutrophils form mitochondria-dependent vital NETs to promote breast cancer lung metastasis

Abstract: BackgroundNeutrophils-linked premetastatic niche plays a key role in tumor metastasis, but not much is known about the heterogeneity and diverse role of neutrophils in niche formation. Our study focuses on the existence and biological function of a rarely delved subset of neutrophils, named as tumor-associated aged neutrophils (Naged, CXCR4+CD62Llow), involved in premetastatic niche formation during breast cancer metastasis.MethodsWe explored the distributions of Naged in 206 patients and mice models (4T1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 58 publications
(44 reference statements)
1
57
1
2
Order By: Relevance
“…NETs are not only related to antimicrobial defense but also play a role in non-infectious diseases, including tumor occurrence and development, thrombosis, vasculitis, etch (28)(29)(30). Many NETs deposits have been found in the blood and tumor tissues of many solid tumors (31)(32)(33). Yang et al found that neutrophils of patients with liver cancer, especially those with metastatic liver cancer, release more NETs; in animal experiments, they found that these NETs can capture liver cancer cells, induce cell death resistance, and enhance invasion (34).…”
Section: Discussionmentioning
confidence: 99%
“…NETs are not only related to antimicrobial defense but also play a role in non-infectious diseases, including tumor occurrence and development, thrombosis, vasculitis, etch (28)(29)(30). Many NETs deposits have been found in the blood and tumor tissues of many solid tumors (31)(32)(33). Yang et al found that neutrophils of patients with liver cancer, especially those with metastatic liver cancer, release more NETs; in animal experiments, they found that these NETs can capture liver cancer cells, induce cell death resistance, and enhance invasion (34).…”
Section: Discussionmentioning
confidence: 99%
“…A unique subset of neutrophils regulates the lung metastasis of breast cancer in a mitochondria-dependent way ( 70 ). Tumor-associated aged neutrophils, defined by CXCR4 + CD62L low , increased in the peripheral blood and lung metastasis in the 4T1 breast tumor model and mouse mammary tumor virus-polyoma middle tumor-antigen (MMTV-PyMT) model.…”
Section: Neutrophil Mitochondria-associated Diseasesmentioning
confidence: 99%
“…Immunofluorescence and scanning electron microscope images show that tumor-associated aged neutrophils can capture tumor cells and promote tumor cell retention in the lung through NETs. Moreover, the SIRT1 knockdown can significantly reduce lung metastasis ( 70 ).…”
Section: Neutrophil Mitochondria-associated Diseasesmentioning
confidence: 99%
“…ROS produced by mitochondria and NOX mediate bactericidal activity in neutrophils ( 82 ). In addition, tumor-associated aged neutrophils can trigger mitochondria-dependent vital NET formation, which promotes lung metastasis in breast cancer ( 83 ). Other stimuli — including gram-positive bacteria ( 84 ), parasites ( 85 , 86 ), and heparin ( 87 ) — can also induce rapid NET release.…”
Section: Mechanisms Underlying the Formation Of Neutrophil Extracellu...mentioning
confidence: 99%